Post-stroke rehabilitation of the ankle joint with a low cost monoarticular ankle robotic exoskeleton: Preliminary results - Asín-Prieto, Guillermo; Mercante, Silvana; Rojas, Raúl; Navas, Mariangeles; Gomez, Daiana; Toledo, Melisa; Martínez-Expósito, Aitor; Moreno, Juan C. (Frontiers in Bioengineering and Biotechnology, 2022)
Introduction Stroke generates a high rate of disability and, in particular, ankle spasticity is a sequelae that interferes with the execution of daily activities. Robotic devices have been proposed to offer rehabilitation treatments to recover control of ankle muscles and hence to improve gait function. Objective The aim of this study is to investigate the effects of passive stretching, combined with active and resisted movement, accompanied by visual feedback, by means of playful interactive software using a low-cost monoarticular robot (MEXO) in patients with stroke sequelae and spastic ankle. Methods An open, uncontrolled, non-randomised, quasi-experimental study of six weeks duration has been completed. A protocol has been defined to determine the usability, safety and potential benefits of supplementary treatment with the MEXO interactive system in a group of patients. Nine volunteer patients with sequelae of stroke who met the inclusion criteria were included. They received conventional treatment and in addition also received treatment with the MEXO monoarticular robot three times a week during six weeks. Each session consisted of ten minutes of passive stretching followed by 20 minutes of active movement training with visual feedback (ten minutes active without resistance, ten minutes with resistance) and a final phase with ten minutes of passive stretching. The following variables were measured pre- and post-treatment: joint range of motion and ankle muscle strength, monopodal balance, muscle tone, gait ability and satisfaction with the use of assistive technology. Results Statistically significant improvements were obtained in joint range measured by goniometry and in balance measured by monopodal balance test. Also in walking capacity, through the measurement of travelled distance. Discussion and Significance Device usability and patient safety were tested. Patients improved joint range and monopodal balance. The MEXO exoskeleton might be a good alternative for the treatment of spastic ankle joint in people with a stroke sequela.